White piedra and pediculosis capitis in the same patient - Marques, Silvio Alencar [UNESP]; Richini-Pereira, Virgínia Bodelão [UNESP]; Camargo, Rosângela Maria Pires de [UNESP] (Sociedade Brasileira de Dermatologia, 2012)
Piedra branca é micose superficial causada pelo gênero Trichosporon e caracterizada por nódulos aderidos à haste do pelo. Pediculose capitis é causada pelo Pediculus humanus var. capitis pertencente à subordem Anoplura. Enquanto que a pediculose é enfermidade comum, relatos clínicos de piedra branca são raros. Técnicas de biologia molecular identificaram o agente de piedra branca do presente relato como T.inkin. Os autores apresentam associação de ambas as infestações no mesmo paciente para salientar seus aspectos clínicos distintos.

White piedra is a superficial mycosis caused by the genus Trichosporon. It is characterized by nodules on the hair shaft. Pediculosis capitis is caused by Pediculus humanus var. capitis of the suborder Anoplura. Whereas pediculosis is a common infestation, clinical reports of white piedra are rare. Molecular biology procedures identified T. inkin as the agent of white piedra in this case report. The authors present associations between the two diseases in the same patient in order to highlight their clinical differences.
Piedra branca e pediculose capitis no mesmo paciente
Keywords: Infestações por piolhos; Piedra; Trichosporon; Lice infestations; Piedra; Trichosporon